Enhancing nutrition knowledge and dietary diversity among rural pregnant women in Malawi: a randomized controlled trial - Lillian Ziyenda Katenga-Kaunda; Penjani Rhoda Kamudoni; Gerd Holmboe-Ottesen; Heidi E. Fjeld; Ibrahimu Mdala; Zumin Shi; Per Ole Iversen (BMC, 2021)
Abstract Background In many sub-Saharan African countries, such as Malawi, antenatal care (ANC) services do not deliver sufficient nutrition awareness to improve adequate dietary intake in pregnancy. We therefore compared the effects of supplementary nutrition education and dietary counselling with routine ANC service on nutrition knowledge and dietary intakes among Malawian pregnant women. Methods We used data from a two-armed cluster randomised controlled trial (RCT) of which the intervention group received supplementary nutrition education, dietary counselling and routine ANC services whereas the controls received only routine ANC services. The RCT was conducted in 10 control and 10 intervention villages in Mangochi, Southern Malawi and included pregnant women between their 9th and 16th gestational weeks. We examined the changes in nutrition knowledge and dietary diversity from enrolment (baseline) to study end-point of the RCT (two weeks before expected delivery). We used three linear multilevel regression models with random effects at village level (cluster) to examine the associations between indicators of nutrition knowledge and diet consumption adjusted for selected explanatory variables. Results Among 257 pregnant women enrolled to the RCT, 195 (76%) were available for the current study. The supplementary nutrition education and counselling led to significant improvements in nutrition knowledge, dietary diversity and nutrition behaviour in the intervention group compared with controls. Most women from both study groups had a moderate consumption of diversified foods at study end-point. A significant positive association between nutrition knowledge and consumption of a diversified diet was only observed in the intervention group. Conclusions Nutrition knowledge and dietary diversity improved in both study groups, but higher in the intervention group. Increased nutrition knowledge was associated with improved dietary diversity only in the intervention women, who also improved their nutrition perceptions and behaviour. Antenatal nutrition education needs strengthening to improve dietary intakes in pregnancy in this low resource-setting. Trial registration Clinical trials.gov ID: NCT03136393 (registered on 02/05/2017).